Adaptive alterations in brain structure and function in young people with Tourette Syndrome - Draper, Amelia (2015)
Tourette Syndrome (TS) is a developmental neurological disorder characterised by vocal and motor tics and is associated with cortical-striatal-thalamic-cortical circuit dysfunction and hyper-excitability within cortical motor areas. TS symptoms often become more controlled throughout adolescence until the individual is largely tic-free by early adulthood. It is likely that adaptive changes occur in the development of brain structure and function throughout the critical developmental period of adolescence in people with TS, which leads to tic remission in some individuals. To investigate this I used multiple brain-imaging approaches including diffusion tensor imaging to look at white matter microstructure, T1-weighted anatomical MR imaging to measure cortical grey matter thickness and MR-Spectroscopy (MRS) to measure neurotransmitters of interest (GABA and glutamate) in a group of young people with TS and a typically developing matched control group. Brain function (measures of excitation and inhibition in M1) was also considered by using transcranial magnetic stimulation. A significant positive relationship was found between white matter structural integrity (FA) measured from the body of the corpus callosum that contained projections to M1 or the SMA and motor tic severity. The TS group had increased levels of GABA in the SMA, as measured by MRS, compared to the control group. SMA- GABA levels had a significant positive relationship with FA from the SMA ROI but a negative relationship with TMS measures of cortical excitability during movement preparation. This suggests that those individuals with the least severe tic symptoms also have reduced callosal white matter from the SMA (an area implicated in the production and suppression of tics) in adolescents with TS, which relates to a reduction in task based cortical excitability and a reduction in SMA-GABA compared to those with more severe tics. The results from this thesis suggest that tic-suppression may occur through decreasing excitatory inputs to M1, either through increasing the inhibition (GABA levels) of the SMA, or by decreasing the number of excitatory interhemispheric inputs to sensorimotor regions.